Sensemaking of rework causation in offshore structures: People, Organization and Project - Love, Peter; Smith, J.; Han, S. (2011)
Cost and schedule overruns are norm in offshore hydrocarbon projects. With increasingly complex commercial and contracting arrangements, technical challenges, changing local economic and regulatory conditions and a shift toward project's being undertaken in peak oil frontier regions, the risks of overruns increase. A major factor contributing to such overruns is rework. Twenty three in-depth interviews with leading oil and gas industry practitioners were undertaken to acquire knowledge of their experiences of rework causation in offshore projects. Analysis of the dialogue and narratives obtained enabled a nomenclature for rework causal factors to be classified as People, Organization and Project for different types of offshore structure. The determination of rework causal factors provides the foundations for appropriate risk management strategies in future projects to be determined.